Penyelenggaraan Umrah Dalam Perspektif Hukum Perlindungan Konsumen Pasca PMA No. 8 Tahun 2018 - Agus Suwandono; Susilowati S. Dajaan (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2020)
To give better protection to the prospective participant of the Islamic pilgrimage (‘umrah), the Minister of Religious Affairs has just added consideration to the Consumer Protection Law in enacting the Minister of Religious Affairs’ Regulation No. 8 of 2018. According to the Consumer Protection Law, this research studies the qualification of the Islamic Pilgrimage’s prospective participant and organizer. It also looks at the recourse obtained by the prospective participants from the perspective of the consumer protection law, after the enactment of the Minister of Religious Affairs’ Regulation No. 8 of 2018. This research is using a juridical-normative approach by specifying the study in a descriptive-analytical manner. The result shows that the Consumer Protection Law’s provision qualifies the prospective participant of Islamic pilgrimage (‘umrah) as a consumer, whereby its organizer as a business actor. From the perspective of the Consumer Protection Law, the enactment of the Minister of Religious Affairs’ Regulation No. 8 of 2018 has not yet fully safeguarded the prospective participant’s interests. In conclusion, after bearing into mind that their rights have not yet wholly fulfilled, particularly at the time of departure cancellation. Pemberlakuan PMA No. 8 Tahun 2018 dengan mempertimbangan ketentuan Undang-Undang Perlindungan Konsumen merupakan hal baru diharapkan dapat lebih memberikan perlindungan terhadap calon jemaah umrah. Penelitian ini mengkaji bagaimanakan kualifikasi calon jemaah umrah serta PPIU berdasarkan Undang-Undang Perlindungan Konsumen serta bagaimanakah perlindungan calon jemaah umrah dalam perspektif perlindungan konsumen pasca pemberlakuan PMA No. 8 Tahun 2018. Penelitian ini merupakan penelitian yurudis normatif dengan spesifikasi penelitian deskriptif analitis. Hasil penelitian menunjukkan bahwa calon jemaah umrah dapat dikualifikasikan sebagai konsumen dan PPIU juga dapat dikualifikasikan sebagai pelaku usaha berdasarkan Ketentuan Undang-Undang Perlindungan Konsumen. Perlindungan calon jemaah umrah dalam perspektif perlindungan konsumen pasca pemberlakuan PMA No. 8 Tahun 2018 belum sepenuhnya memberikan perlindungan bagi calon jemaah umrah, mengingat pemenuhan akan hak-hak para calon jemaah umrah tidak dapat terpenuhi terlebih dalam hal terjadinya gagal berangkatnya calon jemaah umrah.